Effects of the main green tea polyphenol epigallocatechin-3-gallate on cardiac involvement in patients with AL amyloidosis - Mereles, Derliz; Buß, Sebastian Johannes; Hardt, Stefan; Hunstein, Werner; Katus, Hugo (Clinical research in cardiology, 2010)
Amyloid light chain (AL) amyloidosis is a rare disease with poor prognosis and limited therapeutic alternatives. Recently, one clinical case with cardiac involvement, as well as a compelling evidence of green tea polyphenol, epigallocatechin-3-gallate (EGCG), inducing the formation of benign aggregation products that do not polymerize into fibrils were published. This is a report of the cardiac effects of green tea consumption in these patients.